The Effectiveness of Module and Webinar on the Management of Dental Health Emergency in Children with Down Syndrome - Ramadhani, Aulia; Rizky, Beta Novia (Indonesian Journal of Dental Medicine, 2020)
Background: In this COVID-19 pandemic, dental care is one of the affected health treatments due to its high risk of exposure to the virus. This demotivates many parents to participate in regular dental visit, particularly in children with Down Syndrome, due to the high risk of exposure. Therefore, health education is needed for the parents to provide appropriate first aid in the event of dental health emergency in children with down syndrome. Purpose: To increase the knowledge of parents with Down Syndrome children towards Dental Emergency. Methods: This was a semi-research study using descriptive methods and comparison of the pre-test and post-test. This research involved 241 persons. The intervention carried out using modules and emergency dentistry procedures for children with Down Syndrome, packaged in an interactive webinar designed for parents and caregivers. We used paired t-test to determine the significance of the improvement in understanding of the subject matter. Results: There was a significant increase in the understanding of the subject matter from a mean of 5.9 to 9.5 (P <0.05). Conclusion: The program was effective in improving the understanding on the management of dental health emergency in children with down syndrome.